Modernism and Totalitarianism Rethinking the Intellectual Sources of Nazism and Stalinism, 1945 to the Present - Shorten, R.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Modernism and Totalitarianism evaluates a broad range of post-1945 scholarship. Totalitarianism, as the common ideological trajectory of Nazism and Stalinism, is dissected as a synthesis of three modernist intellectual currents which determine its particular, inherited character.
Keywords: Russia—History.; Europe, Eastern—History.; Europe—History.; History, Modern; World politics; Historiography; Political science; Russian, Soviet, and East European History; European History; Modern History; Political History; Historiography and Method; Political Science